The global view of the United States - Sexton, J (Cambridge University Press, 2005)
In the past decade, 'internationalizing' or 'globalizing' American history has become the mantra of the historical profession. This essay reviews this new body of literature that situates American history within a global framework, searches for connections between the United States and the rest of the world, and explores how American practices and culture have been exported. The 'globalizing' project, it shall be argued, has helped historians move beyond the limiting concept of American exceptionalism, whilst providing new explanations for the distinct and, at times, unique, history of the United States. It has also shed new light on the history of American foreign relations. Though historians need to balance the international with the national and better apply transnational methods to the study of the nineteenth century, the global perspective has already added a new texture to our understanding of American history.